Effect of different laser treatments on the shear bond strength of zirconia ceramic to resin cement - Mahnaz Hatami; Mohammadhossein Lotfi-Kamran; Abdolrahim Davari; Meisam Molazem (Wolters Kluwer Medknow Publications, 2021)
Background: Several techniques such as sand blast, silicoating, and laser irradiation have been introduced for reliable bond between zirconia and resin cement. This study aimed to assess and compare the effect of three types of lasers on the shear bond strength (SBS) of zirconia to resin cement. Materials and Methods: In this in vitro study, 55 zirconia disks (6 mm diameter × 3 mm thickness) were randomly divided into five groups: control (1), sandblast (2), carbon dioxide (CO2) (3), erbium-doped yttrium aluminum garnet (Er: YAG) (4), and neodymium-doped yttrium aluminum garnet (Nd: YAG) (5) laser irradiation. The surface morphology of one specimen from each group was evaluated by a scanning electron microscope. Zirconia disks were cemented to composite using Panavia F2. SBS test was performed at a crosshead speed of 1 mm/min after 24 h storage in distilled water and thermocycling. The data were analyzed by one-way analysis of variance and post hoc Tukey's HSD tests (α = 0.05). Results: The mean SBS values of the groups such as sandblast, Er: YAG, Nd: YAG, and CO2 lasers and control were 6.64 MPa, 6.63 MPa, 4.98 MPa, 4.39 MPa, and 2.32 MPa, respectively. No significant difference was observed between sandblast and Er: YAG laser and between Nd: YAG and CO2 lasers. Conclusion: All lasers increased SBS values of zirconia to resin cement in comparison to the untreated surface. Er: YAG laser was the most effective laser treatment on the bond strength equal to that of sandblast.